Lightweight multifunctional polypropylene/carbon nanotubes/carbon black nanocomposite foams with segregated structure, ultralow percolation threshold and enhanced electromagnetic interference shielding performance. (16th June 2020) - Ju, Jiajun; Kuang, Tairong; Ke, Xipeng; Zeng, Min; Chen, Zhou; Zhang, Shuidong; Peng, Xiangfang
Abstract: Lightweight polypropylene (PP) composite materials are preferred to other polymer-matrix composites, in the conductive and electromagnetic interference (EMI) shielding industries, due to their pronounced advantages. However, facile and high-efficiency fabrication of low-density multifunctional PP composite foams, for EMI shielding, remains a challenge. In this study, we fabricated lightweight polypropylene (PP)/carbon nanotubes (CNTs)/carbon black (CB) nanocomposite foams by combining high-speed mechanical mixing, structural manipulation and solid-state supercritical carbon dioxide (ScCO2 ) foaming. Due to the "brick and mud" dense structure formed by high-speed mechanical mixing and structure manipulation, we obtained a low density (0.082–0.101 g/cm 3 ) after solid-state ScCO2 foaming in the nanocomposite foams containing hybrid nanofiller (1:1). Specifically, segregated synergistic conductive networks were observed in the nanocomposite foams. With such networks, the nanocomposite foams containing hybrid nanofiller (1:1) exhibited the best electrical properties ( 6.67 × 10 −3 S/cm at 5 wt% hybrid filler), and the lowest percolation threshold (0.016 vol%) compared with other systems. Moreover, the nanocomposite foams containing 5 wt% hybrid nanofiller (1:1) showed enhanced specific EMI shielding effectiveness ( 72.23 dB·cm 3 /g at X band), and absorption-dominated shielding characteristic. Furthermore, we found a good thermal insulation performance (61.2 mW·m −1 ·K −1 ) and compressive properties ( 37.1 MPa·g −1 ·cm 3 at 50% strain). Overall, our work provides a simple and versatile strategy for fabricating high-performance PP-based nanocomposite foams. These foams present lightweight, ultra-low percolation threshold, high strength, thermal insulation and good EMI shielding properties.